The enhancement of insulin sensitivity by stevioside from Stevia rebaudiana Bertoni in in vitro and in silico models / Nabilatul Hani Mohd Radzman - Mohd Radzman, Nabilatul Hani (Institute of Graduate Studies, UiTM, 2018)
The adoption of unhealthy, sedentary lifestyles has triggered the prevalence of metabolic diseases like diabetes and obesity. A condition referred to as insulin resistance has been found to be the precursor to these diseases. It commonly manifests itself in most if not all Type 2 diabetic cases. A cure is yet to be found and side effects from current drugs create complications among patients. Thus, alternative therapies from natural, plant-based products like stevioside are becoming a more preferred option. Stevioside that is extracted from Stevia rebaudiana Bertoni has impeccable sweetening potential, which provides an interesting aspect to its proposed antidiabetic potentials. Hence, in-depth investigations were conducted to analyse how stevioside can manifest its effects towards insulin sensitivity in in-vitro and in-silico models. Like many herbal products, scientific data on stevioside’s efficacies has been scarce. Its safety of consumption was hence tested through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay on 3T3-L1 adipocytes as an in-vitro model. No IC₅₀ was observed as cell viability was only slightly reduced, signifying its non-cytotoxicity towards adipocytes. Preceding the assay, the cells were tested using Oil Red O to confirm differentiation which was also successfully achieved. Stevioside was observed to increase glucose uptake in adipocytes better than a drug both in normal an insulin resistant states based on the glucose uptake assay that was conducted. Through Western blotting, expression of the phosphorylated tyrosine (pY20) protein on the insulin receptor (IRβ) was also observed to be enhanced by stevioside. This suggests that stevioside has a high probability of interacting with the insulin receptor in improving insulin sensitivity and increasing glucose uptake…